APLIKASI GIBERELIN DAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN AKLIMATISASI TAHAP II PISANG RAJA (Musa paradisiaca L.) VAR. KINALUN - Nurbaiti, Rini; Sasmita, Ellen Rosyelina (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Kinalun Raja Banana, cultivated by the Balitbangtan Subang, is resistant to Fusarium wilt. Cultivation yields can be achieved through tissue culture propagation, with acclimatization being a critical stage. The appropriate growing media and gibberellin growth regulators are required to support the growth of banana plants during the acclimatization stage. This research examine the interaction between gibberellin concentration and growing media composition and to determine the appropriate gibberellin concentration and media composition for the second stage of Raja Kinalun banana acclimatization. The research used a Split Plot Design. The main plot was the gibberellin concentration (40 ppm, 60 ppm, and 80 ppm). The subplots was different comparasion of media compositions Sand: Charcoal: Cocopeat, with the ratios M1 (1:1:1), M2 (1:2:1), and M3 (1:2:2). The results showed that at 40 DAP, there was an interaction between the gibberellin concentration treatment and the growing media composition on the parameter of the number of leaves of Raja Kinalun bananas. The concentration of gibberellin at 80 ppm shows higher results compared to the concentration of gibberellin at 40 ppm in plant height parameter. The growing media composition of Sand : Rice Husk Charcoal : Cocopeat (1:2:2) showed the best results for plant height.